A Case of Giant Colonic Muco-submucosal Elongated Polyps Associated with Intussusception - Joo Heon Kim; Seung Yun Lee; Je Ho Jang; Hyun Young Han; Dong Wook Kang (Korean Society of Pathologists & the Korean Society for Cytopathology, 2016)
Colonic muco-submucosal elongated polyp (CMSEP), a newly categorized non-neoplastic colorectal polyp, is a pedunculated and elongated polyp composed of normal mucosal and submucosal layers without any proper muscle layer. We herein report a giant variant of CMSEP associated with intussusception in the rectosigmoid colon, with a review of the literature. A 48-year-old woman underwent a laparoscopic low anterior resection due to multiple large submucosal polypoid masses associated with intussusception. Grossly, the colonic masses were multiple pedunculated polyps with a long stalk and branches ranging in size from a few millimeters to 14.0 cm in length. Microscopically, there was no evidence of hyperplasia, atypia, or active inflammation in the mucosa. The submucosal layers were composed of edematous and fibrotic stroma with fat tissue, dilated vessels, and lymphoid follicles.